Robust detection in asynchronous CDMA multipath fading channels - Yong-Suk Moon; Kaveh, M.; Nelson, L.B. (1999 IEEE International Conference on Acoustics, Speech, and Signal Processing. Proceedings. ICASSP99 (Cat. No.99CH36258), 1999)
This paper presents a robust detection approach in the presence of transmission delay estimation errors in asynchronous CDMA frequency selective Rayleigh fading channels. The transmission delays in asynchronous channels need to be estimated in practice and are subject to estimation errors, which may cause severe performance degradation for most detectors assuming perfect synchronization. As the fundamental framework of the robust detector, an asynchronous subspace detection scheme based on oblique projection is introduced and examined in comparison with the conventional RAKE receiver and the multipath decorrelator. The performance degradation of the subspace detector due to delay estimation errors is also investigated. The robust detector shows reliable performance even when the errors are much larger than those of delay estimation algorithms like MUSIC, and it is not affected by the near-far problem.